Characterisation of liquid food colour from digital images - Segura, Luis Ignacio (2017)
The characteristic colour of translucent liquid foods is defined as the colour values at infinite depth, where the liquid depth and the background effects are surpassed. A measurement cell with variable depth was built, and the L*a*b* colour was measured from digital images. Colour versus depth was fitted to an exponential equation, from which the characteristic colour was obtained. Thirteen different liquids were tested with this methodology and compared with spectrophotometer measurements. The average total colour difference between approaches was 50.85 ± 18.89. Image analysis led to more realistic predictions, and a high correlation between Hue angle values was obtained for most samples, with the exception of only one.